A protocol for the development of a critical thinking assessment tool for nurses using a Delphi technique. (21st April 2017) - Jacob, Elisabeth; Duffield, Christine; Jacob, Darren
Abstract: Aim: The aim of this study was to develop an assessment tool to measure the critical thinking ability of nurses. Background: As an increasing number of complex patients are admitted to hospitals, the importance of nurses recognizing changes in health status and picking up on deterioration is more important. To detect early signs of complication requires critical thinking skills. Registered Nurses are expected to commence their clinical careers with the necessary critical thinking skills to ensure safe nursing practice. Currently, there is no published tool to assess critical thinking skills which is context specific to Australian nurses. Design: A modified Delphi study will be used for the project. Methods: This study will develop a series of unfolding case scenarios using national health data with multiple‐choice questions to assess critical thinking. Face validity of the scenarios will be determined by an expert reference group of clinical and academic nurses. A Delphi study will determine the answers to scenario questions. Panel members will be expert clinicians and educators from two states in Australia. Rasch analysis of the questionnaire will assess validity and reliability of the tool. Funding for the study and Research Ethics Committee approval were obtained in March and November 2016, respectively. Discussion: Patient outcomes and safety are directly linked to nurses' critical thinking skills. This study will develop an assessment tool to provide a standardized method of measuring nurses' critical thinking skills across Australia. This will provide healthcare providers with greater confidence in the critical thinking level of graduate Registered Nurses.